2019
DOI: 10.1101/516740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The projected economic and health burden of uncontrolled asthma in the United States

Abstract: Rationale: Despite effective treatments, a large proportion of asthma patients do not achieve sustained asthma control. The 'preventable' burden associated with lack of proper control is likely taking a high toll at the population level. Objective:We predicted the future health and economic burden of uncontrolled asthma among American adults for the next 20 years. Methods:We built a probabilistic model that linked state-specific estimates of population growth, asthma prevalence rates, and distribution of asthm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…visits and hospitalizations for children are consistently cited as causing high costs to families and communities related to lost school days, parents' loss of wages, and healthcare access and expenditures. [31][32][33] Previous intervention data focused on students with chronic conditions like asthma have demonstrated reduced morbidity, absenteeism, and exacerbations with various electronic messaging and transmission of health care plans. 6,[34][35][36] In this study, school nurse access to the EHR allowed them to obtain school health forms independently, view updated medical information, and access school-related orders without contacting or causing time burdens on clinicians and clinics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…visits and hospitalizations for children are consistently cited as causing high costs to families and communities related to lost school days, parents' loss of wages, and healthcare access and expenditures. [31][32][33] Previous intervention data focused on students with chronic conditions like asthma have demonstrated reduced morbidity, absenteeism, and exacerbations with various electronic messaging and transmission of health care plans. 6,[34][35][36] In this study, school nurse access to the EHR allowed them to obtain school health forms independently, view updated medical information, and access school-related orders without contacting or causing time burdens on clinicians and clinics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Allergic diseases have caused a tremendous socioeconomic burden as well. For example, researches have shown the United States has spent over $960 billion annually on asthma management [10] . COVID-19 outbreak was declared a global pandemic after the first case of Coronavirus Disease 2019 (COVID- 19) was identified in Wuhan, Hubei Province, China, in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma-attributable deaths and disability-adjusted life-years rates were 6.48 and 297.92 per 100,000 persons in the Global Burden of Disease Study 2017, respectively [1]. A recent study demonstrated that American adolescents and adults with uncontrolled asthma are estimated to be associated with a total economic burden of $963.5 billion and 15.46 million quality-adjusted life years lost over the next 20 years [2]. Therefore, identifying independent factors for developing asthma is a public health priority in order to reduce the substantial burden (secondary to asthma itself) this has on patients and society.…”
Section: Introductionmentioning
confidence: 99%